Equal antipyretic effectiveness of oral and rectal acetaminophen: a randomized controlled trial [ISRCTN11886401] - Malaeb Shadi; Mahfoud Ziyad; Sabra Ramzi; Tamim Hala; Nabulsi Mona; Fakih Hadi; Mikati Mohammad (BMC, 2005)
Abstract Background The antipyretic effectiveness of rectal versus oral acetaminophen is not well established. This study is designed to compare the antipyretic effectiveness of two rectal acetaminophen doses (15 mg/kg) and (35 mg/kg), to the standard oral dose of 15 mg/kg. Methods This is a randomized, double-dummy, double-blind study of 51 febrile children, receiving one of three regimens of a single acetaminophen dose: 15 mg/kg orally, 15 mg/kg rectally, or 35 mg/kg rectally. Rectal temperature was monitored at baseline and hourly for a total of six hours. The primary outcome of the study, time to maximum antipyresis, and the secondary outcome of time to temperature reduction by at least 1°C were analyzed by one-way ANOVA. Two-way ANOVA with repeated measures over time was used to compare the secondary outcome: change in temperature from baseline at times1, 2, 3, 4, 5, and 6 hours among the three groups. Intent-to-treat analysis was planned. Results No significant differences were found among the three groups in the time to maximum antipyresis (overall mean = 3.6 hours; 95% CI: 3.2-4.0), time to fever reduction by 1°C or the mean hourly temperature from baseline to 6 hours following dose administration. Hypothermia (temperature < 36.5°C) occurred in 11(21.6%) subjects, with the highest proportion being in the rectal high-dose group. Conclusion Standard (15 mg/kg) oral, (15 mg/kg) rectal, and high-dose (35 mg/kg) rectal acetaminophen have similar antipyretic effectiveness.